Forensic age determination of human inflicted porcine bruises inflicted within 10 h prior to slaughter by application of gene expression signatures. (October 2018) - Barington, Kristiane; Jensen, Henrik E.; Skovgaard, Kerstin
Abstract: Prediction-models based on gene expression profiles from experimental bruises are capable of determining the age of bruises with a precision of ±2 h. However, these models have not yet been applied on tissue from pigs in forensic cases requested by the police. We applied two prediction-models, based on mRNA expression of 13 (prediction-model no. 1) and 4 genes (prediction-model no. 2) involved in inflammation, on forensic cases of porcine bruises in order to determine if gene expression profiles can be used for age determination in forensic cases. Subcutaneous fat tissue from bruises notified to the police was sampled: 1) within 6 h after slaughter (group no. I, n = 142), and 2) after freezing the skin for up to 1 year (group no. II, n = 40). qPCR of genes involved in inflammation was performed to predict the bruise age after partial least squares analysis. mRNA expression data were obtained for 52.8% and 7.5% bruises in group nos. I and II, respectively. Prediction-model no. 2, based on the mRNA expression of Selectin E, Selectin P, Interleukin 6 and Nuclear Factor Kappa Beta Subunit1, was most suitable for predicting the age of bruises within 8 h prior to slaughter. In conclusion, mRNA expression profiles can assist in estimating the age of bruises. However, when applying gene expression signatures in forensic cases the age estimate should be interpreted together with histological manifestations. Subcutaneous tissue must be stabilized hours after the bruises are detected in order to obtain mRNA of a sufficient quality. Highlights: Age estimation of porcine bruises based on mRNA expression data was evaluated. Subcutaneous fat tissue was sampled from human inflicted bruises on pigs. mRNA expression of four genes resulted in plausible age estimates of bruises in pigs. Tissue should be stabilized within hours after slaughter to preserve mRNA.